Analysis of Charge Pump Topologies for High Voltage Mobile Microphone Applications - Toft, Jakob K.; Jorgensen, Ivan H. H. (Elektronika ir Elektrotechnika, 2021)
This paper presents a novel analysis of charge pump topologies for very high voltage capacitive drive micro electro-mechanical system microphones. For the application, the size and power consumption are sought to be minimized, and a voltage gain of 36 is achieved from a 5 V supply. The analysis compares known charge pump topologies, taking into consideration on resistance of transistors and parasitic capacitances of transistors and capacitors in a 180 nm silicon-on-insulator process. The analysis finds that the Pelliconi charge pump topology is optimal for generating very high bias voltages for micro electro-mechanical system microphones from a low supply voltage when the power consumption and area are limited by the application.